The anode is more beneficial to the advanced treatment of wastewater containing antibiotics by three-dimensional electro-biofilm reactor: Degradation, mechanism and optimization. (February 2022) - Yang, Shumin; Huang, Qingling; Feng, Yan; Ren, Xuefeng; Wang, Jiaoping; Yu, Yanzhen
Graphical abstract: Highlights: The effect of electric polarity and microbial community in 3DE-BAF were investigated. The synergistic mechanism of the particulate bioelectrodes was illustrated. The duck farm wastewater was taken as the treatment object for advanced treatment. Exploring the effect of electric field polarity on biological of advanced treatment. Abstract: The three-dimensional electrode biological aerated filter (3DE-BAF) has the potential to overcome inherent limitations of conventional electrochemical and biofilm methods. Electrochemical means could enhance the performance and sustainability of biofilm technologies and stimulate the spread of new applications in (waste) water treatment. This paper describes the construction and performance of 3DE-BAF in the treatment of simulated wastewater represented by tetracycline (TC). This is followed by a discussion of electrode performance, the electron transport mechanism and the electrode's effect on the biological community of 3D-EBAF. Given the gap between experimental studies and practical applications, the enlarged anode 3DE-BAF named 3DEAE-BAF reactor was applied with good results to duck farm wastewater. This study could provide guidance as to developing new methods to construct a highly stable 3DE-BAF. The paper concludes that improved 3DE-BAF technology is promising for advanced treatment of livestock wastewater containing antibiotics.